Bakti untuk Negeri 80 Tahun RI: Pemanfaatan AI untuk Penguatan Kapasitas Ilmiah - arjulayana, Arjulayana; N. Sofianto, Eko Wahyu; Kusumaningsih, Dewi; Halawa, Kerisman; Dayu Rahma Turista, Dora; Diansyah, Tengku Mohd; Baharuddin, Baharuddin; Arifin, Jaenal; Abid, Nuskhan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This article describes the community service activities carried out by the Mendeley Advisor Community Indonesia entitled